“So I had to give it up”: The role of social support for career persistence or attrition in a qualitative sample of second career teachers - Bauer, Catherine; Trösch, Larissa Maria; Aksoy, Dilan (Swiss Journal of Educational Research, 2021)
This qualitative study uses the Job Demands-Resources framework to examine social support and its role in career retention or attrition among Swiss second career teachers (SCTs). In many countries, including Switzerland, great efforts are made to bring professionals from other occupational fields into teaching. As a result, the number of SCTs is growing, as are speculations about their skills, resources, and career persistence. A qualitative content analysis of 23 semi-structured interviews shows that support from colleagues and principals is a crucial job resource for SCTs, but seems to be positively associated with work engagement and career retention only if it is offered in forms that are sensitive to SCTs’ own needs and skills. Implications for SCT training and job induction are discussed.